PTU-111 A review of chronic hepatitis b virus infection in children in ireland. (22nd June 2015) - Finnegan, R; Tuite, K; Liddy, R; Goode, M; Rochford, A; McDonagh, S; Butler, K; Gavin, P
Abstract : Introduction: Although the majority of children with hepatitis B virus (HBV) infection remain asymptomatic, serious complications such as cirrhosis and hepatocellular carcinoma can occur in later life. Longterm follow up is important to identify these complications early. In Ireland, pregnant women are screened antenatally for HBV. Children born to HBV infected mothers are referred to the Rainbow Clinic. Method: Data on all children with chronic HBV infection, attending the Rainbow Clinic from 2002 to 2014, were retrospectively reviewed using a standard data collection sheet. Chronic HBV infection is defined as HBsAg-positivity for greater than 6 months. Children with only one clinic visit or with HIV co-infection were excluded. Results: 63 children with chronic HBV infection attended the Rainbow clinic between 2002 and 2014 (age range, 6 months-17 years).6 children were excluded (4 single clinic attendance; 2 HIV co-infection). 34 children (60%) were male. 13 children (23%) with chronic HBV were born in Ireland. The majority (44, 77%) were children immigrating to Ireland from overseas: Africa, 16; Central Asia, 14; Eastern Europe, 7; Unknown, 7. HBV was acquired vertically in 35 (61%) children and horizontally in 2. Parental HBV status was unknown in 22 children (15 adoptees).19 children had siblings with chronic HBV infection. 9 of 13 (69%) children born in Ireland received recommended prophylactic IVIG and HBV vaccine at birth. 4 (31%) received no prophylaxis. Birth details from children born outside of Ireland show suboptimal post natal prophylaxis in all: 13 of 16 received no prophylaxis and 3 received HBV vaccine alone. All 57 children had biochemistry performed twice a year. Abdominal ultrasound scans (USS) were performed in 49 children (86%).5 had abnormal USS (coarse echogenicity, 3; splenomegaly, 2). Liver biopsy was performed in 4 children with elevated ALT and high HBV VL. Biopsies showed fibrosis (3) or minimal inflammation (1). USS was normal in 3 of the 4 cases with abnormal biopsy. 3 children received antivirals (3TC) for fibrosis (2) and to reduce risk of transmission (1). Conclusion: Immigration to Ireland accounts for the majority of paediatric HBV infection in this country. The majority of chronic HBV infection in children results from vertical transmission. Failure of postnatal prophylaxis remains a significant problem. Available evidence shows that 100% of foreign-born and 30% of Irish-born children with chronic HBV did not received recommended IVIG and vaccine prophylaxis. 4 children (7%) developed complications of chronic HBV. The need for improved diagnostic tools to identify children at risk of complicated HBV liver disease is again evidenced by failure of USS to identify those children with biopsy-proven abnormalities. Disclosure of interest: None Declared.